The future role of psychiatrists in Europe in the light of the European Pact for Mental Health and Well-being - Caldas de Almeida, J. M. (Die Psychiatrie, 2014)
The European Pact for Mental Health and Well-being, launched in 2008, expresses a commitment of the EU and Member States to implement a mental health strategy in Europe. Recognizing that the level of mental health and well-being in the population is a key resource for the success of the EU as a knowledge-based society and economy, the Pact concludes that action for mental health and well-being at EU-level needs to be developed by involving policy makers and all relevant stakeholders. Given the specific content of their discipline and the prestige they have in our societies, psychiatrists will certainly have a key role in the development of the strategies proposed by the Pact. The purpose of this paper is to review the background, objectives and outcomes of the European Pact for Mental Health and Well-being, and reflect on the future role of psychiatrists in the light of its implementation.
Keywords: Role of psychiatrists; European Pact; mental health